What is communication? Investigations with kindergarten children - Kaźmierczak, Monika (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
Matthew Lipman’s P4C (Philosophy for Children) method, which in Poland took the names: philosophising with children, philosophical investigations with children, workshops in philosophy, workshop classes in philosophy, workshops on philosophical research, is based on a discussion in which children are the active participants and creators of the classes. In the course of the investigations, one can observe children’s communication behaviour in the dialogue, the level of language and communication skills, the specificity of the child’s thinking and the ability to negotiate or interpret meanings in a peer group. The conducted research on communication shows that for five- and six-year-old children ‘communication’ is primarily about building relationships and reciprocity of linguistic actions.